2006
DOI: 10.1111/j.1538-7836.2006.02153.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged prophylaxis with dalteparin to prevent late thromboembolic complications in patients undergoing major abdominal surgery: a multicenter randomized open‐label study

Abstract: Summary. Background: Patients undergoing major abdominal surgery carry a high risk of venous thromboembolism (VTE), but the optimal duration of postoperative thromboprophylaxis is unknown. Objectives: To evaluate the efficacy and safety of thromboprophylaxis with the low molecular weight heparin (dalteparin), administered for 28 days after major abdominal surgery compared to 7 daysÕ treatment. Patients/Methods: A multicenter, prospective, assessor-blinded, open-label, randomized trial was performed in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
202
1
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 348 publications
(226 citation statements)
references
References 22 publications
10
202
1
13
Order By: Relevance
“…58, N o 5, octobre 2015 lost patients in either group could have had dramatic effects on the results either way. The FAME study 8 found a relative risk reduction of 55%, but again the number of patients who dropped out was significant. In a third study, the number of patients who were included in the outcome assessment was only one-third of the total.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…58, N o 5, octobre 2015 lost patients in either group could have had dramatic effects on the results either way. The FAME study 8 found a relative risk reduction of 55%, but again the number of patients who dropped out was significant. In a third study, the number of patients who were included in the outcome assessment was only one-third of the total.…”
Section: Discussionmentioning
confidence: 96%
“…However, the existing literature has not reported an increased bleeding risk, 8,[12][13][14]21 and the consequences of VTE can be lethal. In the Cochrane meta-analysis, 14 the rate of bleeding events in the treatment group was 4.1% (25 of 614 patients) compared with 3.7% (23 of 628 patients) in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations